CeO2−δ as Electron Donor in Co0.07Ce0.93O2−δ Solid Solution Boosts Alkaline Water Splitting - Gege Su; Yichao Hou; Jie Yin; Jiayi Yang; Zhenglong Li; Xin Du; Xin Zhang; Pinxian Xi; Chun‐Hua Yan (Advanced Science)
Abstract Optimizing the electronic structure with increasing intrinsic stability is a usual method to enhance the catalysts’ performance. Herein, a series of cerium dioxide (CeO2−δ) based solid solution materials is synthesized via substituting Ce atoms with transition metal (Co, Cu, Ni, etc.), in which Co0.07Ce0.93O2−δ shows optimized band structure because of electron transition in the reaction, namely Co3+ (3d64s0) + Ce3+ (4f15d 06s0) → Co2+ (3d74s0) + Ce4+ (4f05d06s0), with more stable electronic configuration. The in situ Raman spectra show a stable F2g peak at ≈452 cm−1 of Co0.07Ce0.93O2−δ, while the F2g peak in CeO2−δ almost disappeared during HER progress, demonstrating the charge distribution of *H adsorbed on Co0.07Ce0.93O2−δ is more stable than *H adsorbed on CeO2−δ. Density functional theory calculations reveal that Co0.07Ce0.93O2−δ solid solution increases protonation capacity and favors for formation of *H in alkaline media. General guidelines are formulated for optimizing adsorption capacity and the volcano plot demonstrates the excellent catalytic performance of Co0.07Ce0.93O2−δ solid solution. The alkaline anion exchange membrane water electrolysis based on Co0.07Ce0.93O2−δ/NiFe LDH realizes a current density of 1000 mA cm−2 at ≈1.86 V in alkaline seawater at 80 °C and exhibits long‐term stability for 450 h.